Synthesis, analgesic and anti-inflammatory activities of substituted benzoylthioureas - Tutuk Budiati; Suzana .; Siti Surdijati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Three compounds (i.e. benzoylthiourea, 4-nitrobenzoylthiourea, and 4-chlorobenzoylthiourea) have been synthesized from ammonium thiocyanate, substituted benzoyl chlorides, and ammonia as starting materials. The structures of sythesized compounds were confirmed by means of ultra-violet, infrared, magnetic resonance, and mass spectroscopy. All compounds were evaluated for their analgesic and anti-inflamatory activities by tail-flick technique and carragenan-induced paw oedema test respectively. Substitution of p-NO2 and p-Cl group to benzoylthiourea increased the analgesic and anti-inflamatory activities. The two compounds, 4-nitrobenzoylthiourea and 4-chlorobenzoylthiourea, were significantly more potent as analgesic but their antiinflamatory actvity was weaker than Na-diclofenac.Keywords: benzoylthioureas, p-Cl dan p-NO2substituents, analgesic and anti-inflamator activities